Reparation of radial head chronic fracture-dislocation of ulnar joint using bone autografts - Matelenok, Ievgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
In the treatment of chronic elbow fracture-dislocation important factor in restoring joint function is the reconstruction of damaged bone formation. Objective:to evaluate the use of autograft for the radial hard bone defects in the case of chronic elbow fracture-dislocation. Methods:we observed three patients with chronic elbow fracture-dislocation with terms of 1 to4 months after the injury. Two patients in the acute period after injury in other hospital underwent forearm dislocation, removal of damaged radial head bone and repositional osteosynthesis of proximal ulnar metaphysis and coronoid processus. Because of imperfect surgery, including removal of the radial head bone, lack of proper follow-up, chronic elbow fracture-dislocations formed. We performed: fracture reosteosynthesis of the proximal ulnar metaphysis, radial head bone autoplasy using the iliac crest, direction of the forearm, external fixation devices installed. In the third patient during the initial treatment head fracture of the left radius without dislocation of forearm diagnosed. During immobilization treatment, dislocated forearm diagnosed only after 3 weeks. In this case, we provided the defect substitution with iliac crest transplants for radial head defect substitution (up to 45 % of its value) dislocation reduced and external device installed for 3 weeks. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Results:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> we didn’t diagnosed recurrent forearm fracture-dislocation after 1<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">–<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">2.5 years follow-up. Radiography determined fusion of maternal bone grafts, joint space was clearly visualized. Limb function restored.